GP88 (progranulin): a novel tissue and circulating biomarker for non–small cell lung carcinoma - Edelman, Martin J.; Feliciano, Josephine; Yue, Binbin; Bejarano, Pablo; Ioffe, Olga; Reisman, David; Hawkins, Douglas; Gai, Qiwei; Hicks, David; Serrero, Ginette (Human pathology, 2014)
GP88 (progranulin) is a growth and survival factor implicated in tumorigenesis and drug resistance. Previous studies showed that GP88 was expressed in breast cancer tissue in inverse correlation with survival. This study evaluates GP88 tissue expression in localized/locally advanced lung cancer and GP88 serum levels in advanced disease. GP88 expression was determined by immunohistochemistry in tumor tissue from non–small cell lung carcinoma (NSCLC) patients, 85 with localized (stage I-II), and 40 with locally advanced disease (stage IIIa) and correlated with clinical outcome. Serum GP88 levels from stage IIIb/IV patients, quantified by enzyme immunoassay were compared with GP88 levels from patients with chronic obstructive pulmonary disease and healthy individuals. GP88 was expressed in more than 80% adenocarcinoma and squamous cell carcinoma in contrast to normal lung or small cell lung cancer. There was a statistically significant inverse association of GP88 expression (GP88 immunohistochemistry score, 3+ versus < 3+) with survival for patients with localized resected NSCLC with hazard ratio (HR) = 2.28 (P = .0076) for disease-free survival and HR = 2.17 (P = .014) for overall survival. A statistically significant decrease in progression-free survival (HR = 2.9; P = .022) for GP88 scores of 3+ versus less than 3+ was observed for stage IIIa after chemoradiotherapy. In addition, serum GP88 was significantly elevated in stage IIIb/IV NSCLC compared with control subjects (49.9 ng/mL versus 28.4 ng/mL; P < .0001). This is the first study demonstrating GP88 tissue and serum expression as a prognostic biomarker in localized and advanced disease. Future research will determine utility of monitoring GP88 and the potential of GP88 expression as a predictive marker for anti-GP88 therapeutics.